PENENTUAN ASPEK UTAMA DALAM MENDESAIN KEMASAN TABARO DANGE KHAS LUWU MENGGUNAKAN - Julyaningsih, Andi Hermina; Hamdani, Ibnu Mansyur; Rismawati (Jurnal Agritechno, 2025)
Dange is a traditional food from Luwu that is commonly consumed by the local community as a complementary dish, often served with kapurung, pacco’, or lawak. Made from sago, dange can serve as a rice substitute, providing a satisfying meal due to the high starch content in sago. Additionally, dange can be a suitable option for a low-glycemic diet, given its low glycemic index, which offers health benefits compared to rice. Despite its benefits, dange is not highly popular in the market. This is influenced by several factors, one of which is the packaging used for dange. Cooked and cooled dange is typically packaged in small, thin plastic bags that are unappealing both in appearance and hygiene. Therefore, this study was conducted to propose an alternative packaging design for dange, with the expectation that improved packaging can enhance its market appeal. Several important aspects need to be considered when designing food packaging, including visual appeal, safety/protective capability, product pricing, environmental friendliness, and ease of use. The dominance of these aspects may vary depending on consumer needs and purchasing power, available capital, the primary purpose of the packaging, and the type of product being packaged. Thus, it is necessary to determine the most critical aspect to focus on in designing packaging that better meets the target requirements. One method that can be used to determine this key aspect is the Analytical Hierarchy Process (AHP). This method allows for more objective decision-making by utilizing the Expert Choice software to analyze and score the evaluations provided by expert respondents. Subsequently, the key aspect identified through the AHP method will be compared with survei data collected from 100 respondents/consumers of tabaro dange products. The AHP results indicate that the safety and protective capability of packaging are the primary aspects to consider in designing packaging for the Luwu specialty tabaro dange, with an inconsistency value of 0.08. This finding aligns with survei data from consumers, where 69% identified product quality as the main factor influencing their purchasing decisions. Notably, product quality is heavily influenced by the safety and protective properties of its packaging